Kualitas Mikrobiologi dan Karakteristik Sensori Sambal Petis pada Pedagang Gorengan di Kecamatan Tambaksari, Surabaya, Indonesia - Aulia Islamiati Yusuf Pangan; Sri Winarti; Destiana Adinda Putri; Anna Abdilla; Rosyid Wardianto; Maulia Widi (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2026)
Sambal petis is a traditional Indonesian condiment that is frequently consumed with fried snacks. Nevertheless, the risk of microbial contamination may be elevated by an insufficient level of sanitation during the preparation and handling processes. This study aimed to assess sanitation practices, microbiological quality, and sensory characteristics of sambal petis from 26 fried-snack vendors in Tambaksari, Surabaya, Indonesia. Microbiological quality was assessed based on compliance with applicable microbiological standards, while sensory attributes were analyzed using one-way ANOVA followed by Tukey’s HSD test (p < 0.05). In general, sanitation during processing and equipment was moderate (mean score = 2), while food presentation and vending facilities sanitation were poor (mean score = 3). The total microbial count ranged from 5.17 to 6.25 log CFU/g, exceeding the maximum limit specified in SNI 2718:2013 of 3.69 log cfu/g. Furthermore, E. coli was identified in 50% of the samples, while Salmonella sp. Was identified in 46% of the samples. These results correspond to the observed hygiene behaviors, indicating that microbial contamination may be an implication of inadequate sanitation. Sensory evaluation indicated no significant differences for color, whereas texture and aroma varied significantly among samples. These findings emphasize the importance of effective hygiene, sanitation, and microbiological control measures throughout the food handling chain.